TRANSFORMASI INOVASI:PEMANFAATAN LIMBAH BATU BARA MENJADI PUPUK - Wentasari, Risa; Zadzali, Helmi; Sidiq, Egi Nur Muhamad; Anam, Khairul; Sridanti, Irma Lisa; Agusta, Herdhata; Sudradjat; Hariyadi; Bintoro, Mochamad Hasjim (University of Prof. Dr. Hazairin, SH, 2024)
This literature study aims to review technological developments in the use of coal as fertilizer. The method used in this study is a systematic review. Article searches were carried out using Google Scholar with the keywords